2007
DOI: 10.1088/0953-8984/19/48/486001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deposition dynamics on epitaxial growth

Abstract: The dynamic effects, such as the steering and the screening effects during deposition, on an epitaxial growth (Cu/Cu(001)), is studied by kinetic Monte Carlo simulation that incorporates molecular dynamic simulation to rigorously take the interaction of the deposited atom with the substrate atoms into account. We find three characteristic features of the surface morphology developed by grazing angle deposition: (1) enhanced surface roughness, (2) asymmetric mound, and (3) asymmetric slopes of mound sides. Rega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…We observed the screening effect, which plays a vital role in a DLA as verified by simulations 28 . Two-dimensional sketch schematic diagrams are shown in Figure 3 a, b, respectively.…”
Section: Resultssupporting
confidence: 74%
“…We observed the screening effect, which plays a vital role in a DLA as verified by simulations 28 . Two-dimensional sketch schematic diagrams are shown in Figure 3 a, b, respectively.…”
Section: Resultssupporting
confidence: 74%
“…[33][34][35]38 The resulting fast edge diffusion enhances the mound instability at normal incidence 5 and also enhances the regularity and ordering of the resulting islands and ripples. 17,18,22 In summary, we have carried out extensive simulations of a model of oblique-incidence metal ͑100͒ growth in order to understand the effects of steering and flux-focusing due to attraction as well as shadowing on the surface morphology. We have also studied the dependence of the surface morphology on a variety of deposition parameters including the azimuthal angle, growth temperature, and flux, as well as deposition angle and film thickness.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the extremely time-consuming nature of these simulations, only very recently has it become possible to extend these simulations to multilayer growth. 17,18 Recently, we have used a simplified model with ballistic deposition 19 in order to show that many of the qualitative and semiquantitative features observed in high-angle obliqueincidence Cu/Cu͑100͒ growth by van Dijken et al 7,8 can be explained by geometrical ͑shadowing͒ effects. Our results also indicated that the formation of ͑111͒ facets is crucial to the formation of ripple structures at large angles of incidence.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much interest in understanding the detailed mechanisms controlling surface morphology in epitaxial growth in order to optimize device performance [1,2]. It is generally known that the incoming process of energetic depositing atoms and the accompanying surface diffusion are important steps to determine the morphology of the films grown on the surface [3,4].…”
Section: Introductionmentioning
confidence: 99%